GREAT EURASIAN POWER IN THE WHIRLWIND OF CHANGE: RUSSIA’S MISSION IN THE 21st CENTURY - A. V. Torkunov (Vestnik MGIMO-Universiteta)
The article addresses the issue of historical context of the Russian foreign policy and its practical implications. The author points out that the current political developments within the international system cannot be understood properly without assessing the historical trajectory of the Russian identity. The article divided into three parts that demonstrate the importance of the contextual approach to the Russian foreign policy. The first part deals with the changes in international power balance and the need to conceptualize the new normal without suppressing opposing narratives. The second part assess the practical consideration of such a conceptualization with the aim of mitigating the current tensions between the Russian Federation and the Western states. The third part presents an overview of the Russian approach towards tong-term international stability, distributional international justice and mutual respect.The author concludes that profound change in the international system did not bring considerable alteration in the Russian strategic culture and strategic vision. The article also reassesses the widespread idea of colonialism as the core elements of the Russian strategic thinking. The historical context of the Russian foreign policy proves the opposite view that the vision of self in Russia is much more about bridging the gaps and facilitating mutual dialog. Moreover, the author believes that the main reason for that approach is the relatively stable international position of Russia (in terms of centuries, rather than decades).